Cooperative Stitching: Spontaneous Wireless Connections for Small Co-Located Groups. - Hinckley, Ken; Ramos, Gonzalo (2006)
Forming spontaneous connections between wirelessly networked devices is an important problem for ubiquitous computing. We explore cooperative stitching, which allows small collocated groups to easily create one-to-one or oneto-many connections between devices by performing simple dragging gestures to or from the top of the screen (to initiate or accept a connection, respectively). A usability study finds that users prefer cooperative stitching to a technique that requires physically reaching to the other devices, or to selecting names of devices from long lists.